2022
DOI: 10.1159/000528662
|View full text |Cite
|
Sign up to set email alerts
|

Higher Prepubertal IGF-1 Concentrations Associate to Earlier Pubertal Tempo in Both Sexes

Abstract: Introduction: Pubertal onset is triggered by multiple neuroendocrine interactions. The role of prepubertal IGF-1 in this process has not been explored in both sexes. Our objective is to analyze the association of prepubertal IGF-1 concentration with age at thelarche (B2) and menarche (M) in girls and age at gonadarche (G2) in boys. Methods: Longitudinal study (n=1196 boys and girls) within the Growth and Obesity Chilean cohort Study (GOCS). At ages ≈ 6.7 years blood sample for IGF-1. Subjects analyzed into 4 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…IGF-1 levels are associated with age and play a key role in growth 68 . A few longitudinal studies have shown that higher IGF-1 levels are related to earlier puberty onset 69 and higher breast cancer risk 70 . Oily fish were positively associated with circulating IGF-I concentrations 71 .…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 levels are associated with age and play a key role in growth 68 . A few longitudinal studies have shown that higher IGF-1 levels are related to earlier puberty onset 69 and higher breast cancer risk 70 . Oily fish were positively associated with circulating IGF-I concentrations 71 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, GH secretion in individuals with obesity is reduced [ 95 ]. Interestingly, greater levels of IGF-1 before puberty were demonstrated to be associated with an earlier onset of thelarche and menarche among girls [ 96 ]. Similarly, higher growth before puberty was linked to lower ages of thelarche and menarche [ 96 ].…”
Section: Non-metabolic Complications Of Obesity In Childrenmentioning
confidence: 99%
“…Interestingly, greater levels of IGF-1 before puberty were demonstrated to be associated with an earlier onset of thelarche and menarche among girls [ 96 ]. Similarly, higher growth before puberty was linked to lower ages of thelarche and menarche [ 96 ]. In the case of boys, higher pre-pubertal IGF-1 levels were associated with earlier gonadarche and increased height [ 96 ].…”
Section: Non-metabolic Complications Of Obesity In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with obesity are usually taller than their normal-weight peers, which may be caused by increased circulating levels of IGF-1 [3,20,52,53], as GH release is suppressed, which implies that their height is rather GF-independent [20] or might be caused by increased adrenal androgens [54]. One study [30] reports the higher stature of obese children but also lower IGF-1 compared to a normal-weight control group.…”
Section: Children's Height and Its Relationship With Pubertymentioning
confidence: 99%